Analysis Of Types Of Carotenoid Pigments In Crab Sesarmops sp From Manado By Coast - Adrian, Melinda Margareta; Paransa, Darus S. J; Paulus, James J. H; Kawung, Nickson J.; Bara, Robert A.; Kepel, Rene Ch. (Sam Ratulangi University, 2021)
Carotenoid pigments are a group of pigments that are yellow, orange, and red-orange in color. Pigments are natural dyes found in plants and animals, extracts of carotenoid pigments can be separated by chromatographic methods where the common chromatographic methods in determining the type of pigment are Column Chromatography (CC) and Thin Layer Chromatography (TLC). The purpose of this study was to determine the types of pigments contained in the carapace extract of the male crab Sesarmops sp. The Sesarmops sp crab has a brown dorsal carapace with blackish-brown leg spots known as mangrove crabs. Crabs in the Sesarmidae family have a carapace formation and wide legs, do not have swimming legs, and have a pair of claws that are faded purple, the presence of these colors can be identified as containing carotenoid pigments. The results of this study obtained the content of carotenoid pigment 25.2 g/gr and the value of the concentration of carotenoid pigment in the male crab extract Sesarmops sp 10.99 g. The results of the separation of the total pigment extract using column chromatography obtained the types of pigments -carotene, Ekinenon, Zeaxanthin, and Astaxanthin. Keywords: Column Chromatography (CC); Carotenoids; Sesarmops sp AbstrakPigmen karotenoid adalah sekelompok pigmen yang berwarna kuning, oranye dan merah oranye. Pigmen adalah zat warna alami yang terdapat pada tumbuhan dan hewan, ekstrak pigmen karotenoid dapat dipisahkan dengan metode kromatografi yang dimana metode kromatografi umum dalam menentukan jenis pigmen adalah Kromatografi Kolom (KK) dan Kromatografi Lapis Tipis (KLT). Tujuan dari penelitian ini untuk mengetahui jenis-jenis pigmen apa saja yang terdapar pada ekstrak karapas kepiting jantan Sesarmops sp. Kepiting Sesarmops sp memiliki karapas dorsal bewarna coklat dengan bintik kaki coklat kehitaman yang dikenal sebagai kepiting mangrove. Kepiting dalam keluarga sesarmidae memiliki bentukan karapas dan kaki yang lebar tidak memiliki kaki renang serta memiliki sepasang capit berwarna ungu pudar, adanya warna tersebut kepiting dapat diidentikasikan mengandung jenis pigmen karotenoid. Dari hasil penelitian ini mendapatkan kandungan pigmen karotenoid 25,2 dan nilai konsentrasi pigmen karotenoid pada ekstrak kepiting jantan Sesarmops sp 10,99 . Hasil pemisahan dari ekstrak pigmen total menggunakan kromatografi kolom didapatkan jenis pigmen β-karoten, Ekinenon, Zeaxantin dan Astaxantin